Two Targets, One Hit: new Anticancer Therapeutics to Prevent Tumorigenesis Without Cardiotoxicity - Szabó, Zoltán; Hornyák, Lilla; Miskei, Márton; Székvölgyi, Lóránt (Frontiers in Pharmacology, 2021)
A serious adverse effect of cancer therapies is cardiovascular toxicity, which significantly limits the widespread use of antineoplastic agents. The promising new field of cardio-oncology offers the identification of potent anti-cancer therapeutics that effectively inhibit cancer cell proliferation without causing cardiotoxicity. Future introduction of recently identified cardio-safe compounds into clinical practice (including ERK dimerization inhibitors or BAX allosteric inhibitors) is expected to help oncologists avoid unwanted cardiological complications associated with therapeutic interventions.